The Role of Development Skills in Social Work Practice and Education in Finland - Aino Ritala-Koskinen; Heli Valokivi (Social Work and Society, 2006)
In this article our perspective is to discuss the intensification and perspectives of development work in the social sector in Finland and the question of social work skills in relation to the development in practice. Within the last decades Finland has experienced far reaching changes in relation to development work and social planning. What are the implications of this development for the master's degree programmes in social work? This forms the context in which we as members of the team of social work educators [1] have been planning our social work curriculum in Pori which has started in autumn 2004. The Department of Pori was founded [2] in 2004 as part of the Faculty of Social Sciences at the University of Tampere. The department offers master's degree programmes in social work as well as in social policy and sociology. The City of Pori, which is located on the western coast of Finland, represents a new location of social work teaching in Finland. Instead of a single university Pori has the Pori University Consortium [3] , in which five different Finnish universities [4] and different fields are presented with 2400 students and 190 staff members. The Pori University Consortium has expressly regional targets. The many-sided development and raising the competitive potential of the Satakunta region by increasing the academic know-how are the reasons why the city of Pori promotes university education. The Department of Pori at Tampere University gives high priority to questions of welfare services and working life. This follows the development plan the city of Pori has been supporting through different projects and the funding of the professorship on welfare services for five years. In this context the education of qualified social workers (master in social work) and experts in welfare services is a new challenge.